ORIENTATION PROCESS AND PROFESSIONAL INSERTION CAPACITY OF YOUNG GRADUATES ON THE LABOR MARKET - Edith Faure MEFEUTO; Vandelin MGBWA (Universitaria Publishing House, Craiova, 2023)
This article analyzes the impact of factors inherent to the orientation modalities on the professional insertion of young graduates in the job market. Although university institutions believe that they are providing young graduates with adequate training so that they can be competitive on the job market, it appears that they still have difficulty entering the job market. However, university training is developed without taking into account the orientation processes such as the personal interests of the graduate. This results in unemployment. The study is part of an explanatory approach based on a mixed design. It was carried out among 200 graduates of the departments of Art and Archaeology of the Falsh, Tourism and Hospitality. The questionnaire and the semi-structured interviews of individual types collected information from 200 participants and another 5 for the interview, respectively. The results show positive correlations between professional interest and access to employment r (200) = .353, p < .001; commitment r (200) = .355, P < .001; job retention r (200) = .293, p < .001; and finally professional insertion r (200) = .405, p < .001. It should be noted that orientation and university training policies are not sufficient if the young graduate does not feel involved in the process. The study suggests the involvement of guidance actors in the training programs; to focus these trainings on the existing opportunities on the labor market.